The handbook of phonetic sciences - Hardcastle, William J., 1943-; Laver, John; Gibbon, Fiona E. (Blackwell handbooks in linguistics., 2012)
Thoroughly revised and updated, the second edition of The Handbook of Phonetic Sciences provides an authoritative account of the key topics in both theoretical and applied areas of speech communication, written by an international team of leading scholars and practitioners. Combines new and influential research, along with articulate overviews of the key topics in theoretical and applied areas of speech communicationAccessibly structured into five major sections covering: experimental phonetics; biological perspectives; modelling speech production and perception; linguistic phonetics; and speech.